2001
DOI: 10.1080/09658210042000058
|View full text |Cite
|
Sign up to set email alerts
|

Short-term memory and working memory as indices of children's cognitive skills

Abstract: In the current literature, empirical and conceptual distinctions have been drawn between a more or less passive short-term memory (STM) system and a more dynamic working memory (WM) system. Distinct tasks have been developed to measure their capacity and research has generally shown that, for adults, WM, and not STM, is a reliable predictor of general cognitive ability. However, the locus of the differences between the tasks has received little attention. We present data from children concerning measures of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
42
3
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(50 citation statements)
references
References 34 publications
4
42
3
1
Order By: Relevance
“…This common variance might be based on some visual modality-specific perceptual ability that is used to spot colors in arrays and vowels in visually presented sequences. Cowan, Elliot, et al (2005) found that contrary to conventional wisdom based on the adult literature, simple auditory span correlated well with intelligence measures in children who were too young to engage in sophisticated rehearsal (see also Hutton & Towse, 2001). The children in the present paper are at the upper end of this range (see, e.g., Ornstein & Naus, 1978) and, similar to Cowan, Elliott, et al (2005), memory for lists in children (visual and auditory spans and performance in the auditory-only condition) were significantly related to intelligence, as shown in Table 2.…”
Section: Correlations and Regressionsmentioning
confidence: 98%
See 1 more Smart Citation
“…This common variance might be based on some visual modality-specific perceptual ability that is used to spot colors in arrays and vowels in visually presented sequences. Cowan, Elliot, et al (2005) found that contrary to conventional wisdom based on the adult literature, simple auditory span correlated well with intelligence measures in children who were too young to engage in sophisticated rehearsal (see also Hutton & Towse, 2001). The children in the present paper are at the upper end of this range (see, e.g., Ornstein & Naus, 1978) and, similar to Cowan, Elliott, et al (2005), memory for lists in children (visual and auditory spans and performance in the auditory-only condition) were significantly related to intelligence, as shown in Table 2.…”
Section: Correlations and Regressionsmentioning
confidence: 98%
“…We suggest that for that reason even digit span had a high correlation with intellectual aptitudes for second-and fourth-grade children, though not for sixth-grade children or adults (Cowan, Elliott, et al, 2005; cf. Hutton & Towse, 2001). …”
mentioning
confidence: 99%
“…In complex span tasks, participants are asked to encode lists of memoranda (which are to be recalled later) while intermittently performing some kind of distracting processing activity (Case, Kurland, & Goldberg, 1982;Daneman & Carpenter, 1980). In general, complex span performance is inferior to that of simple span, which measures immediate recall of memoranda after their presentation in the absence of distracting processing activity (e.g., Duff & Logie, 2001;Hutton & Towse, 2001;La Pointe & Engle, 1990).…”
Section: How Does Processingmentioning
confidence: 99%
“…In complex span tasks, participants are asked to encode lists of memoranda (which are to be recalled later) while intermittently performing some kind of distracting processing activity (Case, Kurland, & Goldberg, 1982;Daneman & Carpenter, 1980). In general, complex span performance is inferior to that of simple span, which measures immediate recall of memoranda after their presentation in the absence of distracting processing activity (e.g., Duff & Logie, 2001;Hutton & Towse, 2001;La Pointe & Engle, 1990).Consequently, and perhaps unsurprisingly, the presence of the processing activity within a complex span task tends to cause forgetting of memoranda presented during the task.One reason for the substantial research interest in the complex span task is that performance on this measure is typically a strong correlate of measures of intelligence in adults (Bayliss, Jarrold, Gunn, & Baddeley, 2003;Kyllonen & Christal, 1990;Süß, Oberauer, Wittmann, Wilhelm, & Schulze, 2002) and of academic achievement in children (Bayliss et al, 2003; Bull, Epsy, & Wiebe, 2008;Swanson, 2008). Furthermore, many would argue that complex span performance is a significantly stronger correlate of these abilities than is simple span (Conway, Cowan, Bunting, Therriault, & Minkoff, 2002; Engle, Tuholski, Luaghlin, & Conway, 1999; Oberauer, Schulze, Wilhelm, & Süß, 2005), indicating that the forgetting caused by the imposition of processing within a complex span task increases its predictive power.…”
mentioning
confidence: 99%
“…So 'working memory' refers to a system that both temporarily stores and processes information. This, amongst other features, distinguishes it from short-term memory (Dehn 2011, Hutton andTowse 2001), which is taken to be a passive storage system. There is a good deal of dispute about how long exactly the period of time is that the information in working memory is available for cognitive processing; views range from 1-2 seconds, to roughly 15 seconds, to 30 seconds.…”
mentioning
confidence: 99%